(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2014)
The rehabilitation process of hearing-impaired and implanted children indicates difficulties and some necessary conditions for the establishment of vocals echoic, tact and mand responses. In this context, a bibliographical review over instruction procedures of operants echoic, tact and mand was made in the periodical JABA’s database in three phases: Initial search over the period of 1968 to 2012, identifying 306 articles; selection of the abstracts about the target operants’ teaching procedures, with 45 selected; and reading and analyzing of the selected studies. Tact and mand were the target operants in 80% of the studies, and echoic was a prerequisite in 70% of the studies; 10 articles reported teaching of more than one verbal operant target individually, or with transference control procedures. Only two studies focused on hearing-impaired participants, suggesting investment on studies about vocal expressive establishment conditions within this population